2016
DOI: 10.1021/jacs.6b09450
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Bonding Controls Selectivity in Heterogeneous Catalysis: Coupling Reactions on Gold

Abstract: Enhancing the selectivity of catalytic processes has potential for substantially increasing the sustainability of chemical production. Herein, we establish relationships between reaction selectivity and molecular structure for a homologous series of key intermediates for oxidative coupling of alcohols on gold using a combination of experiment and theory. We establish a scale of binding for molecules with different alkyl structures and chain lengths and thereby demonstrate the critical nature of noncovalent van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 38 publications
(70 reference statements)
11
73
0
Order By: Relevance
“…The liquid organics were purified according to procedures described previously and the gas phase vapor was leaked in the chamber while monitoring the rise in pressure of the chamber. 31 , 32 Temperature programmed experiments were performed with each reactant to identify its signature products and displacement reactions were preformed to determine the relative binding stability of selected pairs of carboxylates as described in the (ESI † ). The quantitative analysis of the temperature programmed reaction data was performed as described in the ESI.…”
Section: Methodsmentioning
confidence: 99%
“…The liquid organics were purified according to procedures described previously and the gas phase vapor was leaked in the chamber while monitoring the rise in pressure of the chamber. 31 , 32 Temperature programmed experiments were performed with each reactant to identify its signature products and displacement reactions were preformed to determine the relative binding stability of selected pairs of carboxylates as described in the (ESI † ). The quantitative analysis of the temperature programmed reaction data was performed as described in the ESI.…”
Section: Methodsmentioning
confidence: 99%
“…The distance between the backbone of the species and the Cu surface increases when the vdW interactions were excluded, confirming the significant vdW effects on the structures. [26][27][28][29][30][31] The transition states for C-H bond breaking of 1-propoxy and 1-butoxy were reexamined with the updated adsorption structures. The NEB calculations suggested that the transition It is important to emphasize more generally the difficulty in finding the global minimum in the high-dimensional configuration space of adsorption for large molecules.…”
Section: Multiple Basins In the Energy Landscape Of Adsorptionmentioning
confidence: 99%
“…The decomposition of several molecules and the relative stabilities of intermediates in on-surface reactions on Au have recently been attributed to the strong van der Waals (vdW) interaction. [56][57][58][59][60] We therefore investigated the role of dispersion for dissociation II and III by calculating the related adsorption energies with and without inclusion of vdW interaction (Table II), namely, with the PBE + vdW functional and the pure PBE (Perdew-Burke-Ernzerhof) functional (see Appendix, Subsection 4). The adsorption energies of 1, 3, and 4 increase by ≈2.2 eV with PBE compared to PBE + vdW, reflecting strong dispersion interaction with Au(111) and its crucial role for the adsorption process.…”
Section: Role Of Dispersion Interactionmentioning
confidence: 99%